2019
DOI: 10.1002/app.48404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amine‐terminated additives on thermal and mechanical properties of diglycidyl ether of bisphenol A (DGEBA) cured epoxy

Abstract: The present work accounts for the influence of aromatic amide oligomers on the inherent brittleness of cured epoxy. Aromatic and aliphatic amine‐terminated amide oligomers have been prepared by condensation polymerization using isophthaloyl dichloride and two different amines. The oligomers have been characterized using Fourier transform infrared spectroscopy and wide angle X‐ray diffraction analysis. Diglycidyl ether of bisphenol A (DGEBA) is cured with a diamine (4,4′‐oxydianiline) by using different weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The introduction of new molecular chains of different lengths, with pendant groups, aliphatic or aromatic elements, vary many physicochemical and solid-state properties of the composites. For example, heterocyclic and aromatic curing reagents are responsible for higher temperature stabilities than their aliphatic amine alternatives [25]. An increment in the flexible amine content decreases the tensile and flexible strength related to a reduced crosslinking density [26].…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of new molecular chains of different lengths, with pendant groups, aliphatic or aromatic elements, vary many physicochemical and solid-state properties of the composites. For example, heterocyclic and aromatic curing reagents are responsible for higher temperature stabilities than their aliphatic amine alternatives [25]. An increment in the flexible amine content decreases the tensile and flexible strength related to a reduced crosslinking density [26].…”
Section: Resultsmentioning
confidence: 99%
“…The flame retardant is expected to overcome flammability and increase T g of EP. PA, as a thermoplastic engineering resin, is usually used to improve the properties of EP or EP composite due to its excellent performance 22,23 . Therefore, in this paper, a hyperbranched PA oligomer containing DOPO (HPD) was synthesized using ethylene diamine tetraacetic acid (EDTA) and DOPO functionalized with diamines as starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this approach cross‐link density was adjusted by two‐phase separation phenomena and resulted in high elongation at break (>100%) and still acceptable tensile strengths. Recently in another study, Baig et al 28 modified epoxy curing agent with two different amine terminated additives and studied its effects on mechanical and thermal properties of epoxy polymer. They have found that aromatic amine terminated polymers imparted better overall mechanical properties than aliphatic amide polymers.…”
Section: Introductionmentioning
confidence: 99%